Resilience amongst Australian aboriginal youth: an ecological analysis of factors associated with psychosocial functioning in high and low family risk contexts. - Katrina D Hopkins (Public Library of Science (PLoS), 2014)
We investigate whether the profile of factors protecting psychosocial functioning of high risk exposed Australian Aboriginal youth are the same as those promoting psychosocial functioning in low risk exposed youth. Data on 1,021 youth aged 12-17 years were drawn from the Western Australian Aboriginal Child Health Survey (WAACHS 2000-2002), a population representative survey of the health and well-being of Aboriginal children, their families and community contexts. A person-centered approach was used to define four groups of youth cross-classified according to level of risk exposure (high/low) and psychosocial functioning (good/poor). Multivariate logistic regression was used to model the influence of individual, family, cultural and community factors on psychosocial outcomes separately for youth in high and low family-risk contexts. Results showed that in high family risk contexts, prosocial friendship and low area-level socioeconomic status uniquely protected psychosocial functioning. However, in low family risk contexts the perception of racism increased the likelihood of poor psychosocial functioning. For youth in both high and low risk contexts, higher self-esteem and self-regulation were associated with good psychosocial functioning although the relationship was non-linear. These findings demonstrate that an empirical resilience framework of analysis can identify potent protective processes operating uniquely in contexts of high risk and is the first to describe distinct profiles of risk, protective and promotive factors within high and low risk exposed Australian Aboriginal youth.